Pelatihan Desain UI/UX Menggunakan Figma pada SMA PGRI Siborongborong - Samuel V. B. Manurung; Mufria J. Purba; Humuntal Rumapea; Darwis Robinson Manalu; Sri Agustina Rumapea; Indra M. Sarkis S.; Jimmy F. Naibaho; Yolanda Y. P. Rumapea; Arina Prima Silalahi; Agus Syahputra (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
This Community Service Program (PKM) aimed to enhance students’ digital literacy and skills through UI/UX design training using the Figma application for students of SMA PGRI Siborongborong, Tapanuli Utara Regency, North Sumatra. This activity represents the implementation of the Tri Dharma of Higher Education by the Faculty of Computer Science, Universitas Methodist Indonesia Medan, in the form of knowledge and technology transfer to secondary education institutions.The training was conducted over two days using a combination of lectures, demonstrations, and hands-on practice in designing mobile-based application interfaces. The materials covered included an introduction to digital application concepts, the fundamentals of User Interface (UI) and User Experience (UX), and the utilization of key features in Figma to design simple application prototypes. The results indicated that participants were able to understand basic UI/UX concepts and independently produce application interface designs. The students’ enthusiasm and active participation throughout the program reflected a strong interest in developing digital design skills. This activity contributed positively to improving students’ information technology competencies while strengthening collaboration between the university and the school as a community service partner.